The absence of flightless moult in the Ruddy-headed Goose in Argentina and Chile - Summers, Ronald W (Wildfowl, 1982)
The primaries of 14 adult Ruddy-headed Geese Chlophaga rubidiceps from Argentina and Chile were examined. Incomplete moult was carried out in autumn (March) on the breeding ground and in spring (September) on the wintering ground. This moult does not involve a flightless period. Most birds had a combination of old inner and new outer primaries, or new inner and old outer primaries suggesting they moult inner and outer primaries in different seasons, or alternate years.